Levofloxacin Versus Ciprofloxacin-Based Prophylaxis during the Pre-Engraftment Phase in Allogeneic Hematopoietic Stem Cell Transplant Pediatric Recipients: A Single-Center Retrospective Matched Analysis - Alessia G. Servidio; Roberto Simeone; Davide Zanon; Egidio Barbi; Natalia Maximova (MDPI AG, 2021)
Infectious complications are the most common and significant cause of mortality and morbidity after allogeneic hematopoietic stem cell transplantation (HSCT). Antibacterial prophylaxis in pediatric cancer patients is a controversial issue. Our study compared the outcomes of levofloxacin versus ciprofloxacin prophylaxis in allogeneic HSCT pediatric recipients treated for hematological malignancies. A total of 120 patients received levofloxacin prophylaxis, and 60 patients received ciprofloxacin prophylaxis. Baseline characteristics such as age, gender, primary diagnosis, type of conditioning, donor type, stem cell source, and supportive care of the patients were similar, and duration of antibiotics prophylaxis was similar. Both prophylaxis regimens demonstrated the same efficacy on the risk of febrile neutropenia and severe complications such as sepsis, the same rate of overall mortality, hospital readmission, and length of hospital stay. Levofloxacin prophylaxis was associated with significantly lower cumulative antibiotic exposure. The median of Gram-positive infection-related antibiotic days was 10 days in the levofloxacin group versus 25 days in the ciprofloxacin group (p < 0.0001). The median of Gram-negative infection-related antibiotics was 10 days in the levofloxacin group compared with 20 days in the ciprofloxacin group (p < 0.0001). The number of days with body temperature ≥38 °C was significantly less in the levofloxacin group (p < 0.001).